Using Rationale to Assist Student Cognitive and Intellectual Development - Burge, Janet; Brinkman, Bo (Human Technology, 2010)
One of the questions posed at the National Science Foundation (NSF)-sponsored workshop on Creativity and Rationale in Software Design was on the role of rationale in supporting idea generation in the classroom. College students often struggle with problems where more than one possible solution exists. Part of the difficulty lies in the need for students to progress through different levels of development cognitively and intellectually before they can tackle creative problem solving. Argumentation-based rationale provides a natural mechanism for representing problems, candidate solutions, criteria, and arguments relating those criteria to the candidate solutions. Explicitly expressing rationale for their work encourages students to reflect on why they made their choices, and to actively consider multiple alternatives. We report on an experiment performed during a Data Structures course where students captured rationale.